2024
DOI: 10.1186/s12885-024-12327-1
|View full text |Cite
|
Sign up to set email alerts
|

Glycometabolism and lipid metabolism related genes predict the prognosis of endometrial carcinoma and their effects on tumor cells

Xuefen Lin,
Jianfeng Zheng,
Xintong Cai
et al.

Abstract: Background Glycometabolism and lipid metabolism are critical in cancer metabolic reprogramming. The primary aim of this study was to develop a prognostic model incorporating glycometabolism and lipid metabolism-related genes (GLRGs) for accurate prognosis assessment in patients with endometrial carcinoma (EC). Methods Data on gene expression and clinical details were obtained from publicly accessible databases. GLRGs were obtained from the Genecard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 85 publications
(83 reference statements)
0
1
0
Order By: Relevance
“…LPCAT1 has been implicated in various cancers, including hepatocellular carcinoma, breast cancer, head and neck squamous cell carcinoma, lung squamous cell carcinoma, lung adenocarcinoma, esophageal squamous cell carcinoma, cervical cancer, endometrial cancer, clear cell renal cell carcinoma (ccRCC), and acute myeloid leukemia. Elevated LPCAT1 expression is consistently associated with a poorer prognosis in patients with these cancers [ 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 ]. Knockdown studies have demonstrated the essential role of LPCAT1 in the proliferation, migration, invasion, epithelial–mesenchymal transition (EMT) of cancer cells, and overall tumor growth [ 78 , 85 , 90 , 95 , 96 ].…”
Section: 1-acylglycerol-3-phosphate O-acyltransferases and Lysophosph...mentioning
confidence: 99%
“…LPCAT1 has been implicated in various cancers, including hepatocellular carcinoma, breast cancer, head and neck squamous cell carcinoma, lung squamous cell carcinoma, lung adenocarcinoma, esophageal squamous cell carcinoma, cervical cancer, endometrial cancer, clear cell renal cell carcinoma (ccRCC), and acute myeloid leukemia. Elevated LPCAT1 expression is consistently associated with a poorer prognosis in patients with these cancers [ 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 ]. Knockdown studies have demonstrated the essential role of LPCAT1 in the proliferation, migration, invasion, epithelial–mesenchymal transition (EMT) of cancer cells, and overall tumor growth [ 78 , 85 , 90 , 95 , 96 ].…”
Section: 1-acylglycerol-3-phosphate O-acyltransferases and Lysophosph...mentioning
confidence: 99%